2012
DOI: 10.1038/ejhg.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the genetic make-up of North-East Sardinia using a large set of haploid and autosomal markers

Abstract: Sardinia has been used for genetic studies because of its historical isolation, genetic homogeneity and increased prevalence of certain rare diseases. Controversy remains concerning the genetic substructure and the extent of genetic homogeneity, which has implications for the design of genome-wide association studies (GWAS). We revisited this issue by examining the genetic make-up of a sample from North-East Sardinia using a dense set of autosomal, Y chromosome and mitochondrial markers to assess the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
4
10
0
Order By: Relevance
“…In our knowledge, only one study has previously assessed genome-wide patterns of homozygosity in the Sardinian population [5]. Although the criteria used for the identification of RoHs are slightly different between the present study and that of Pardo and colleagues, the results of the two studies are consistent.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In our knowledge, only one study has previously assessed genome-wide patterns of homozygosity in the Sardinian population [5]. Although the criteria used for the identification of RoHs are slightly different between the present study and that of Pardo and colleagues, the results of the two studies are consistent.…”
Section: Discussionsupporting
confidence: 63%
“…In general, Sardinia appears characterized by a large internal homogeneity [5], [7], like all isolated populations, even though other investigators suggested the presence of genetically different subpopulations in the island [6], [48]. Recently several genome-wide studies have been performed on Sardinian population taking advantage of the genetic homogeneity of the island using also large cohort of individuals [49], [50], [51], [52], [53].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reconstructions of the genetic structure of Italy agreed on two points: the peculiarity of the population of Sardinia – due to a distinct background and a high degree of isolation [58], [59] – and the clinal pattern of variation in the Italian Peninsula, which has been explained by differential migration patterns [17], [18] although some genetic discontinuity due to local drift and founder effects have been described [16], [19], [20]. This study represents a significant upgrade on the knowledge of the genetic structure of Italy for the following reasons: the wide sampling coverage (coupled to a detailed sampling strategy), the high number of typed markers and the innovative methodological approach.…”
Section: Discussionmentioning
confidence: 94%
“…[15][16][17][18] These have revealed distinct genetic structures that can provide guidance on using these populations for mapping the genes for complex diseases. We decided to examine the genetic structure and founder effects within the NL population by comparing genome-wide SNP data with that from Irish, British, Native American and other HapMap3 populations.…”
Section: Introductionmentioning
confidence: 99%